2003
DOI: 10.1152/jn.00114.2002
|View full text |Cite
|
Sign up to set email alerts
|

Cerebellar Control of Constrained and Unconstrained Movements. I. Nuclear Inactivation

Abstract: The aim of this study was to determine in monkeys if inactivation of dentate and lateral interposed deep cerebellar nuclei preferentially impairs certain movements relative to others. Constrained movements of the digits were trained with digits, hand, and elbow constrained in a cast. Simplemovements were flexion of Thumb or Index. A compoundmovement was simultaneous flexion of Thumb+Index. An unconstrained movement consisted of a reach to, pinch of, and retrieval of a small food reward (Reach+Pinch). In two mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2004
2004
2013
2013

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(19 citation statements)
references
References 32 publications
0
19
0
Order By: Relevance
“…Thach et al (1992) reported no deficit in finger movements but did see walking on the paw dorsum. Goodkin and Thach (2003) reported deficits in all types of limb movements including finger movements, while Monzée et al (2004) reported deficits in upper limb but not finger movements. Muscimol can spread large distances (Martin, 1991), and the different reports may reflect inactivation of different regions of the nuclei.…”
Section: Rdao Inactivationmentioning
confidence: 99%
“…Thach et al (1992) reported no deficit in finger movements but did see walking on the paw dorsum. Goodkin and Thach (2003) reported deficits in all types of limb movements including finger movements, while Monzée et al (2004) reported deficits in upper limb but not finger movements. Muscimol can spread large distances (Martin, 1991), and the different reports may reflect inactivation of different regions of the nuclei.…”
Section: Rdao Inactivationmentioning
confidence: 99%
“…observed after basal ganglia lesions in both rodents 77,78 and primates. [79][80][81][82][83] In primates, lesions inducing dystonia were located in the posterior sensorimotor putamen. 84 Overall, the role of the basal ganglia in dystonia is largely supported by convergent evidence from different sources.…”
Section: Is Dystonia Caused By Defects In the Basal Ganglia Cerebellmentioning
confidence: 99%
“…Inactivation of cerebellar nuclei using muscimol in monkeys has yielded conflicting results. Goodkin and Thach (2003) found that muscimol injections in the dentate nucleus can give rise to impaired timing of finger movements, causing delays of up to 50 ms. Monzée et al (2004) reported no immediate effect (within 20 min) of muscimol injections into the dentate nucleus and observed impaired grip force performance on trials where the animal's arm showed tremor and dysmetria and was unrestrained. However, if the forearm was restrained, the grip force behavior was seemingly normal (Monzée et al, 2004).…”
Section: Neurophysiological Questionsmentioning
confidence: 99%